Ekspresi Verbal Ritual Pacu Jalur dan Sistem Kognisi Pendukungnya - yance, Imelda (Universitas 17 Agustus 1945 Surabaya, 2020)
This study focused on verbal expressions contained in the Pacu Jalur traditional ritual in Kuantan Singingi, Riau Province. The aim is to describe the form and meaning of the Pacu Jalur lexicon, its function and the cognitive system that is reflected in it.. This research was conducted with an anthropological linguistic approach and with a qualitative-descriptive method. The verbal form of Pacu Jalur rituals is a number of lexicons (words and groups of words) that are unique to the culture of the Rantau Kuantan people that are used denotatively or connotatively. The meaning of the lexicon is related to the culture of the Orang Rantau Kuantan. The lexicon includes spells, actions, and objects. Pacu Jalur Ritual is a medium for asking for directions, asking permission, maintaining safety, waking up the mambang, allying with the mambang, predicting, and even defeating the opponent's jalur magically (mamompan). The function of the Pacu Jalur ritual is productive, protective, and destructive. The results of this study show the relationship between language and culture (linguistic relativity). The Pacu Jalur traditional ritual provides an understanding of some of the supporting cognitive systems related to religion, the supernatural, humans, and the environment. Keywords: ritual of Pacu Jalur tradition, anthropological linguistics, Rantau Kuantan People